2009
DOI: 10.1038/ncb1843
|View full text |Cite
|
Sign up to set email alerts
|

The yeast global transcriptional co-repressor protein Cyc8 can propagate as a prion

Abstract: SummaryAlthough many proteins can misfold into a self-seeding amyloid-like conformation1, only six are known to be infectious, i.e. prions; [PSI+], [PIN+], [URE3], [SWI+] and [HET-s] cause distinct heritable physiological changes in fungi2–4, while PrPSc causes infectious encephalopathies in mammals5. It is unknown if “protein-only” inheritance is limited to these exceptional cases, or represents a widespread mechanism of epigenetic control. Towards this goal, we now describe a new prion formed by the Cyc8 (Ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
195
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(199 citation statements)
references
References 28 publications
(54 reference statements)
3
195
1
Order By: Relevance
“…Expression of peptides with a specific Q-rich region, like the QA-repeat of Gts1p or TCERG1/CA150, might present a strategy to interfere with Htt toxicity. However, regions with QA-repeats may themselves tend to aggregate, as reflected by the aggregation propensity of Gts1p (21,62) and Cyc8p, another yeast prion with a QA-repeat (63). Indeed, expansion of the QA-repeat of TCERG1/CA150 can lead to an earlier onset of HD (60), presumably by placing a burden on the cellular proteostasis system (10).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of peptides with a specific Q-rich region, like the QA-repeat of Gts1p or TCERG1/CA150, might present a strategy to interfere with Htt toxicity. However, regions with QA-repeats may themselves tend to aggregate, as reflected by the aggregation propensity of Gts1p (21,62) and Cyc8p, another yeast prion with a QA-repeat (63). Indeed, expansion of the QA-repeat of TCERG1/CA150 can lead to an earlier onset of HD (60), presumably by placing a burden on the cellular proteostasis system (10).…”
Section: Discussionmentioning
confidence: 99%
“…Prions (Wickner 1994;Coustou et al 1997;Derkatch et al 2001;Du et al 2008;Alberti et al 2009;Nemecek et al 2009;Patel et al 2009;Rogoza et al 2010). Sup35p is a subunit of the translation termination factor; Rnq1p has no known function; Swi1p, Cyc8p, Mot3p, and Sfp1 are transcription factors; and Mca1p is a metacaspase (putative protease).…”
mentioning
confidence: 99%
“…Rnq1p is rich in Q and N residues (hence its name) and had been shown capable of self-propagating aggregation (Sondheimer and Lindquist 2000). Derkatch et al showed that amyloid of Rnq1p was the basis of [PIN+] by applying the above three genetic criteria (Derkatch et al 2001 (Du et al 2008;Patel et al 2009;Suzuki et al 2012). It is expected that this method will be useful in finding prions of other organisms, particularly because the prion domain of Mod5p is not Q/N rich, unlike those of other yeast prions (Suzuki et al 2012).…”
Section: Phenotype Relationshipmentioning
confidence: 99%